SOME ASPECTS OF THE AIDED COMPUTER SOLVING OF ORDINARY DIFFERENTIAL EQUATIONS - JEDYNAK, Radoslaw (Trends in education, 2008)
The article presents the possibilities of utilization of the computer applications to aid the mathematical calculations, on the example of solving ordinary differential equations. Differential equations very often appear in various subjects not only in mathematics, engineering sciences but also natural and different once. Hence the efficient skills of their solving are important.
Keywords: the computer aided of mathematical calculations; Mathematica; MS Excel